Ab initio quantum transport calculations using plane waves. Issue 3 (August 2015) - Garcia-Lekue, A.; Vergniory, M.G.; Jiang, X.W.; Wang, L.W.
Abstract: We present an ab initio method to calculate elastic quantum transport at the nanoscale. The method is based on a combination of density functional theory using plane wave nonlocal pseudopotentials and the use of auxiliary periodic boundary conditions to obtain the scattering states. The method can be applied to any applied bias voltage and the charge density and potential profile can either be calculated self-consistently, or using an approximated self-consistent field (SCF) approach. Based on the scattering states one can straightforwardly calculate the transmission coefficients and the corresponding electronic current. The overall scheme allows us to obtain accurate and numerically stable solutions for the elastic transport, with a computational time similar to that of a ground state calculation. This method is particularly suitable for calculations of tunneling currents through vacuum, that some of the nonequilibrium Greens function (NEGF) approaches based on atomic basis sets might have difficulty to deal with. Several examples are provided using this method from electron tunneling, to molecular electronics, to electronic devices: (i) On a Au nanojunction, the tunneling current dependence on the electrode–electrode distance is investigated. (ii) The tunneling through field emission resonances (FERs) is studied via an accurate description of the surface vacuum states. (iii) Based on quantum transport calculations, we have designed a molecular conformational switch, which can turn on and off a molecular junction by applying a perpendicular electric field. (iv) Finally, we have used the method to simulate tunnel field-effect transistors (TFETs) based on two-dimensional transition-metal dichalcogenides (TMDCs), where we have studied the performance and scaling limits of such nanodevices and proposed atomic doping to enhance the transistor performance.